EVALUATION OF HYPERTENSION PREVENTION & MANAGEMENT STRATEGIES: THE IMPACT OF ANTIHYPERTENSION BEVERAGES AND MORINGA TEA ON MOOD DEVELOPMENT AND IMMUNITY - Jayadi, Yusma Indah; Hasbi Ibrahim; Nadyah Haruna (Homes Journal: Hospital Management Studies Journal, 2025)
Background: Takalar Regency in 2017 the number of hypertension sufferers was 2969 (80%) with 927 men (28%) and 1769 women (61%). Moringa is one of the assets in Maccini Baji Hamlet. It is known that the Moringa plant contains all the nutrients needed to balance blood pressure. Objective: The purpose of this study was to evaluate education related to the prevention and management of hypertension as well as to foster the atmosphere of antihypertensive drinks from Moringa leaves.Method: This research is a quantitative study using purposive sampling technique related to counseling on the prevention and control of hypertension and building an atmosphere for antihypertensive drinks carried out by observation and in-depth interviews related to knowledge, attitudes and actions.Result: The results of the study proved the effect of the boiled water of Moringa leaves on blood pressure in hypertensive patients. The Wilcoxon Statistical Test was carried out at a significance level of α (0.05) with a (p) value of 0.000, so it can be said that there was a significant change between the Moringa leaf decoction and changes in blood pressure in hypertensive patients.Conclusion: Based on the analysis of the Friedmen test, it showed a significant value of 0.000 (p <0.05) so that it can be concluded that there was an increase before and after three months of counseling on prevention and control of hypertension.